A review of COVID-19: a threat to pregnant women? - Kaur, Amanjot; Singh, Jasninder; Shingla, Shweta; Kaur, Mandeep (International Journal of Research in Medical Sciences, 2021)
The outbreak of Coronavirus disease-2019 (COVID-19) has widely spread worldwide. While, mild symptoms have been observed in a majority but on the other hand, the virus may cause severe pulmonary disease. The major concern has been the pregnant women. In this review, we have tried to cover COVID-19 infections transmission, diagnosis, management, prognosis during pregnancy. The evidence on vertical transmission has been lacking. However, physiological changes during pregnancy, make women more vulnerable to this COVID-19. The problem of anxiety also flares up the disease in pregnancy.